TEXNOLOGIYALÍQ TÁLIM BAǴDARÍNDA ARALÍQTAN OQÍTÍWDÍŃ ÁHMIYETLILIGI HÁM ZAMANAGÓY JAǴDAYÍ - Qalmuratova, Xurliman Arıslanbaevna (SCIENCE and SOCIETY, 2026)
The article analyzes the relevance of implementing distance learning in technological education, its current state, and pedagogical potential. Under the conditions of digital technology development, automation of production processes, and modernization of the education system, distance learning is considered an important factor in improving the effectiveness of technological education. The study highlights the advantages and limitations of distance learning tools and proposes ways to overcome them.